Governance and supply chain challenges in aquaculture development in Azerbaijan - Aliyeva, Ilaha (My University, 2026)
Aquaculture has become a key agenda item in modern food systems, addressing food security, rural development and sustainable production. Global fisheries and aquaculture production reached 223.2 million tonnes in 2022 (Food and Agriculture Organization [FAO], 2024). This figure reflects the growing role of aquatic food systems in global food supply. Aquaculture accounted for 51 percent of aquatic animal production in that year (FAO, 2024). This growth is providing a new model of production in the face of pressure on wild capture fisheries. At the same time, aquatic food production provides economic opportunities for nutrition, employment and rural income. Forecasts for 2025–2034 indicate that aquaculture will remain a key driver of fisheries and aquatic products growth (Organisation for Economic Co-operation and Development & FAO [OECD & FAO], 2025). As a result, aquaculture is transforming from a narrow production sector into a broad value chain system. Its success depends on the linkages established between production, inputs, services, processing and market access.